Integrated One Health Surveillance of West Nile Virus and Usutu Virus in the Veneto Region, Northeastern Italy, from 2022 to 2023 - Federica Gobbo; Giulia Chiarello; Sofia Sgubin; Federica Toniolo; Francesco Gradoni; Lidia Iustina Danca; Sara Carlin; Katia Capello; Giacomo De Conti; Alessio Bortolami; Maria Varotto; Laura Favero; et al. (Pathogens)
West Nile virus (WNV) and Usutu virus (USUV) are neurotropic mosquito-borne orthoflaviviruses maintained in an enzootic cycle, in which birds are amplifying/reservoir hosts, while humans and equids are dead-end hosts. As northern Italy, especially the Veneto Region, is considered an endemic area for WNV and USUV circulation, a surveillance plan based on a One Health approach has been implemented since 2008. This work reports the results of entomological, veterinary and human surveillances for WNV and USUV in the Veneto Region in 2022 and 2023, through virological and/or serological examinations. In 2022, 531 human WNV infections were recorded, and 93,213 mosquitoes and 2193 birds were virologically tested, showing infection rates (IRs) of 4.85% and 8.30%, respectively. The surveillance effort in 2023 provided these results: 56 human WNV infections were confirmed, and 133,648 mosquitoes and 1812 birds were virologically tested, showing IRs of 1.78% and 4.69%, respectively. This work highlights the exceptional circulation of WNV in the Veneto Region, due to the new re-introduction of WNV lineage 1 and co-circulation with WNV lineage 2. This paper confirms the efficacy of integrated surveillance for early warning of viral circulation and gives new insights about avian hosts involved in the enzootic cycle of orthoflavivirus in the endemic region of Italy.